2014
DOI: 10.1155/2014/854560
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Ultramicronized Palmitoylethanolamide in Peripheral Neuropathic Pain

Abstract: Introduction. This study evaluates the efficacy of palmitoylethanolamide ultramicronized (PEA-um) as an add-on treatment in patients with diabetic or traumatic neuropathic pain (NP). Methods. 30 patients with chronic NP were assessed with Visual Analogue Scale (VAS), NP Symptom Inventory (NPSI), and Health Questionnaire Five Dimensions (EQ-5D), both at baseline and after 10 and 40 days of treatment with 1200 mg/die of PEA-um. All other therapies were maintained stable during the follow-up period. Results. VAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…It is the failure to control this that creates and keeps neuropathic pain, for which the intervention of PEA is helpful and necessary. Furthermore, PEA normalizes mastcell de- granulation and microglial activation thereby maintaining tissue homeostasys and therefore in a progressive decrease in endogenous production of PEA leads to an inability to regulate mastcells and microglial cells, creating pain symptoms [7,8]. Therefore um-PEA (Ultramicronized Palmithoylethanolamide) is used in those diseases in which the mechanisms of neuroinflammation are present such as neuropathies, by nerve entrapment [9] or dismetabolic [10], toxic [11] and others [12][13][14][15] and some primary headaches [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is the failure to control this that creates and keeps neuropathic pain, for which the intervention of PEA is helpful and necessary. Furthermore, PEA normalizes mastcell de- granulation and microglial activation thereby maintaining tissue homeostasys and therefore in a progressive decrease in endogenous production of PEA leads to an inability to regulate mastcells and microglial cells, creating pain symptoms [7,8]. Therefore um-PEA (Ultramicronized Palmithoylethanolamide) is used in those diseases in which the mechanisms of neuroinflammation are present such as neuropathies, by nerve entrapment [9] or dismetabolic [10], toxic [11] and others [12][13][14][15] and some primary headaches [16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, short‐term efficacy of um‐PEA was also demonstrated in patients with diabetic or traumatic neuropathic pain, where the administration of the formulation (1200 mg·day −1 p.o.) in addition to standard therapies improved both the visual analogue scale and neuropathic pain symptom inventory scores within the first 10 days (Cocito et al, ). Importantly, a pooled data meta‐analysis has recently been performed to evaluate the efficacy and safety of m‐PEA and um‐PEA on pain intensity in patients suffering from chronic and/or neuropathic pain (Paladini et al, 2016).…”
Section: Pea and Pain Perceptionmentioning
confidence: 99%
“…Case reports and open-label studies suggest an effect of ultramicronized PEA (PEA-um) on neuropathic pain, including central pain [7,12,16,32]. Recent systematic reviews in neuropathic pain and PEA [9,16,36] have only identified 2 randomized placebo-controlled trials, both showing efficacy of micronized PEA (PEA-m) in sciatic pain [6,11].…”
Section: Introductionmentioning
confidence: 99%